2005
DOI: 10.1097/01.yct.0000158015.88677.bc
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Attention-dependent Auditory Processing by Electroconvulsive Therapy in Psychotic Depression

Abstract: There is a lack of knowledge about the effect of electroconvulsive therapy (ECT) on auditory event-related potentials (ERPs) in severe psychotic depression. The aim of this study was to investigate both the effect of ECT on attention-dependent ERP (P300) and the correlation of P300 values with depression level. We recorded the auditory ERPs of 23 patients expressing psychotic symptoms and fulfilling the DSM-III-R criteria for treatment-resistant severe major depressive episode before and a week after successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…In auditory ERP studies, authors found a smaller P300 amplitude over Cz in rapid responders to ECT (HDRS = 7, second week) compared to slow responders (HDRS = 7, third and fourth week) and a correlation between the P300 amplitude and the reduction of depressive symptoms after ECT ( 16 , 17 ); the smaller the P300 over C3, the greater the reduction in HDRS scores. Results from the study using TMS-EEG to measure baseline characteristics did not claim for the interest of this measure as a predictive marker of response to ECT ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In auditory ERP studies, authors found a smaller P300 amplitude over Cz in rapid responders to ECT (HDRS = 7, second week) compared to slow responders (HDRS = 7, third and fourth week) and a correlation between the P300 amplitude and the reduction of depressive symptoms after ECT ( 16 , 17 ); the smaller the P300 over C3, the greater the reduction in HDRS scores. Results from the study using TMS-EEG to measure baseline characteristics did not claim for the interest of this measure as a predictive marker of response to ECT ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies included depressive patients with psychotic features, and one included patients with schizoaffective disorder with depression. Severity of illness before ECT was quite homogeneous with mean scores at the 17-item Hamilton Depressive Rating Scale (HDRS 17 ) ranging from 26.9 ( 16 ) to 28.7 ( 26 ) ( N = 3 studies), from 29.3 ( 17 ) to 29.7 ( 21 ) ( N = 2) at 21-item HDRS and from 34.0 ( 25 ) to 38.5 ( 17 ) at the Montgomery–Asberg Depression Rating Scale (MADRS) ( N = 2, excluding the mean score of 18.3 in Miyauchi and colleagues ( 18 ), where pre-ECT vs. post-ECT MADRS scores were not significant. Non-psychiatric comorbidities were described only in one study ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of an explicit definition, authors often defined the term using examples. Psychotic symptoms are most frequently hallucinations and delusions or more specifically, auditory hallucinations and delusions . Others only directly referred to delusions or hallucinations .…”
Section: Resultsmentioning
confidence: 99%
“…Psychotic symptoms are within the general population, 92,95,101,108,181,204,205 on a continuum, and risk factors for developing psychotic disorders . Psychotic symptoms are also symptoms of psychopathological states such as psychosis and psychotic disorders, 98,105,111–113,115,127,138,145,146,149,154,156,162,164,167,169,174,177,179,184,188,189,191–193,196–198 dementia, 103,107,116,117,125,135,137,139,140,152,157,166,168,170,172,173,175,176,186 alongside delirium, substance use, mood disorders, PTSD, personality disorders, medication side effects, and medical conditions such as Parkinson's disease …”
Section: Resultsmentioning
confidence: 99%